(untitled) (Pedagogy of Higher and Secondary Education, 2004)
In the article ways of stimulation of pedagogical situations are considered based on strategy of individuality developing training with application of computer technologies. Authors describe variants of the organization tasked with the approach in vocational training the teacher of music. Efficiency of use of electronic devices as toolkit of the organization of a individuality-guided situation in formation of such parameters of the person o f the teacher as ability to self actualization, a selfestimation, to project new creative tasks comes to light.